2011
DOI: 10.1111/j.1365-2788.2011.01413.x
|View full text |Cite
|
Sign up to set email alerts
|

Factorial validity and consistency of the Maslach Burnout Inventory among staff working with persons with intellectual disability and dementia

Abstract: The use of the MBI-HHS as an instrument for measuring burnout among ID workers has its attraction but also its limitations. In particular, the DP sub-scale should be used with caution because there appear to be wording issues for staff in ID settings that may lead to inconsistent responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
34
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 23 publications
9
34
0
4
Order By: Relevance
“…Weak reliability ratings of the DP scale in previous studies (Chao et al . ) and in the current study also point to the need for more careful examination of this component of burnout.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Weak reliability ratings of the DP scale in previous studies (Chao et al . ) and in the current study also point to the need for more careful examination of this component of burnout.…”
Section: Discussionsupporting
confidence: 51%
“…As in previous studies of burnout (Skirrow & Hatton ; Chao et al . ; Rose ), direct support workers in this study reported relatively low levels of burnout compared with other human service sectors. Based on the normative benchmarks for the survey instrument (Maslach et al .…”
Section: Resultsmentioning
confidence: 51%
“…Note that the personal accomplishment scale is interpreted in the opposite direction, with lower scores more suggestive of burnout. Chao et al (2011) and conducted factor analyses on the MBI-HSS with staff in the developmental disabilities sector and found that it is both reliable and valid, although there has been some critique of the lower reliability of the depersonalization subscale.…”
Section: Instrumentsmentioning
confidence: 98%
“…2008) consider the questionnaire to be psychometrically robust enough for use in diverse countries, and others have concluded that it is a suitable tool for assessing dimensions of burnout in staff working with persons with ID (Hastings et al . 2004; Chao et al . 2011).…”
Section: Introductionmentioning
confidence: 99%